The influence of online social interaction propensity on purchase intention: The moderating role of neuroticism - Yang, Cheng-Liang; Chang, Shu-Ya (Edelweiss Applied Science and Technology, 2025)
This study examines how online social interaction propensity influences consumers’ purchase intentions in E-commerce live-streaming contexts. The research draws on the Social Identity Model of Deindividuation Effects (SIDE) to clarify the psychological mechanisms linking individuals’ online social interaction propensity to their purchasing behavior, with consumer escapism as a mediator and neuroticism as a moderator. A quantitative research design was adopted using survey data from 469 live-streaming commerce users, and structural equation modeling (SEM) was applied to test the proposed relationships. The findings show that online social interaction propensity significantly enhances purchase intention, consumer escapism partially mediates this effect, and neuroticism amplifies the positive association between social interaction and escapism. These results demonstrate that psychological and personality factors jointly shape consumer decisions in interactive digital environments. The study provides both theoretical and practical contributions by enriching the conceptualization of escapism as a consumption motive and offering actionable insights for brands and live-streaming platforms to develop personalized engagement strategies aligned with users’ psychological traits.